Fish Distribution Pattern and Management in the Tinau River, Palpa - Narayan Baral; Hira Bahadur Rana; Dolma Reshmi (Tribhuvan Journal, 2024)
For study direct observation, survey, questionnaire, interviews and discussion method are used to meet the objectives. The main objectives of the study were fish distribution pattern and fish management. The field work was performed between September 2016 to june 2017 of different five stations in Tinau river. Local fishermen were also used for the collection of fishes from sampling sites. Cast net, hook, Bhureli jal and Nets (Jhal) other locally available devices were used for the collection of fish sample. Altogether 5 orders, 9 families, 14 genera and 25 species were found in the study area. Among them 19 fish species from Station I, 16 fish Species from Station II and station III, 10 fish species from Station IV and 7 species from Station V were collected with the help of local fisherman. Fish species such as Channa punctatus, Puntius conchonius and Glyptothorax pectinopterus were found to be clumped in distribution while the rest of the fishes were uniformly distributed. Cyprinids were found to be the most common and dominant among all the species. The human impacts like construction of dam, bridges, riverbed extraction, bank erosion, illegal fishing and use of poisonous chemicals effects on the fish distribution and management directly of the Tinau river. For the management practices like implementation of strict rules and regulations, made ladder for fish passing, construction of fish barrier, plantation, control water pollution and awareness programmes should be done with the help of local people and other institutions. This study helps the local people to pay more attention towards the knowledge about indigenous or locally found fishes and proper management of the Tinau river.